MAGNETIC STORM AND ITS EFFECTS - Azizbek Komiljonov; Muhammad Aziz Kuchkarov; Parvina Amonova; Marvarid Abdurasulova; Kurbonov Jamshit Muhiddinovich (Scholar Express Journals, 2025)
Magnetic storms are phenomena that occur as a result of the impact of high-energy particles and magnetic waves emitted from the Sun on the Earth's magnetic field. This article provides a detailed analysis of the origin of magnetic storms, their effects on the Earth's magnetic field, and their positive and negative impacts on human health and technological systems. Additionally, it outlines the necessary measures for the management and prevention of magnetic storms.
Keywords: Magnetic storm; Solar wind; Geomagnetic disturbance